(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
In this article, every pedagogue is interested in learning and keeping up with the times by giving teachers new innovative information in the process of teaching, professional innovation, modern thinking.